Multiloculated cystic renal tumors of childhood: Has the final word been spoken - Jujju Jacob Kurian; Susan Jehangir; Anila Korula (Wolters Kluwer Medknow Publications, 2018)
Background: Multicystic renal tumors which include cystic nephroma, cystic partially differentiated nephroblastoma (CPDN) and cystic Wilms tumor has been a diagnostic and therapeutic challenge. Histopathological examination has been the only reliable differentiating method. Management of these tumors is still riddled with controversy as a definitive preoperative differentiation between the three has not been possible. Methods: A retrospective evaluation was performed of the treatment strategies employed with nine cases of multicystic renal tumors treated from 2005 to 2015. Results: The median age at presentation was 12 months with all except one being boys. All except two children underwent primary surgery. The median follow-up was 50 months with six children having long-term survival. One child succumbed to the disease process, one died due to an unrelated cause and another was lost to follow-up. Although there was no ambiguity with cases of cystic nephroma (CN) and cystic Wilms tumor, three of the four cases of CPDN had problems. Conclusion: Primary surgery for multicystic renal tumors is safe and should be seriously considered as it prevents overtreatment in cases of CN and early stage CPDN. Further studies are needed to fully understand the biological behavior of CPDN.